Tax Standard Operating Procedures (SOP) at PT Momentum Sample Indonesia - Valentine Candra; Budi Harsono; Sari Dewi (ConCEPt - Conference on Community Engagement Project, 2025)
This project focuses on developing a comprehensive Tax Standard Operating Procedure (SOP) for PT Momentum Sample Indonesia as a response to the company’s lack of formalized tax administration guidelines. Previously, tax-related tasks were performed based on informal habits, which led to inconsistent practices, unclear responsibilities, calculation errors, and increased exposure to administrative sanctions. Through a qualitative methodology involving direct observation, interviews with accounting/tax personnel, and examination of relevant documents, the program identified operational problems and designed standardized procedures for the completion of both periodic (SPT Masa) and annual (SPT Tahunan) tax obligations. The finalized SOP compiles step-by-step procedural narratives, workflow flowcharts, tax rate references, calculation templates, and document archiving standards to improve accuracy, efficiency, and regulatory compliance. Its early implementation yielded notable results, including clearer process mapping, improved accuracy in tax computations, strengthened documentation systems, and the identification of previously overlooked 2023 tax outstanding through structured reconciliation with the Coretax DJP database. These findings show that the SOP functions not only as an operational guideline but also as an effective mechanism for detecting legacy compliance issues. Future recommendations include integrating automated tax features via accounting or ERP systems, conducting periodic internal compliance audits, routinely updating the SOP in line with regulatory developments, enhancing staff capability in digital tax platforms, and reinforcing the company’s digital archiving infrastructure.